Pengaruh Promosi melalui Media Sosial Instagram dan EWOM terhadap Keputusan Berkunjung di PDIKM Kota Padang Panjang - Dina Amalia Syarif; Nidia Wulansari (Lembaga Pengembangan Kinerja Dosen, 2024)
This research was motivated by the discovery of problems related to promotion via social media Instagram and electric word of mouth (ewom) on the decision to visit the documentation center. The aim of this research is to find out and describe the influence of promotion via social media Instagram and electric word of mouth (ewom) on the decision to visit the documentation center. The type of research used is quantitative with a causal associative approach. The type of data used in this research is primary and secondary data. The population of this research is visitors to the Minangkabau culture of PDIKM Padang City. The research sample consisted of 103 consumers with a sampling technique using non-probability sampling using purposive sampling. The data collection technique was carried out using a questionnaire with a Likert scale which had been tested for validity and reliability. Data from this research were processed using SPSS 25.00. The results of this research show that promotion via social media Instagram is in the sufficient category with a value of 3.40, then the electric word of mouth (ewom) variable is in the sufficient category with a value of 3.40, and the decision variable to visit the documentation center is in the sufficient category with a value of 3.40. value of 3.40. The influence of promotion via social media, Instagram and electric word of mouth (ewom) on the decision to visit the documentation center with an adjusted R Square of 49.3% and 50.7% influenced by other factors.